ASSESSMENT OF WORK BEHAVIOR OF STATE CIVIL APPARATUS (ASN) IN THE EMPLOYEE PERFORMANCE TARGET (SKP) AT THE BUREAU OF GOVERNMENT AND REGIONAL AUTONOMY OF THE REGIONAL SECRETARIAT OF EAST JAVA PROVINCE (MAP Observer: Jurnal Penelitian Administrasi Publik, 2022)
The Employee Performance Target (SKP) is a form of the performance appraisal for the State Civil Apparatus (ASN) Based on PP No. 46 of 2011. Work performance assessment contains 60% SKP and 40% Behavioral Assessment. This study aims to determine how the assessment of the behavior of the State Civil Apparatus (ASN) in the Employee Performance Target (SKP) as well as the supporting and inhibiting factors in the behavioral assessment. This study uses a descriptive method with a qualitative approach. Based on the results of this study, it is known that the assessment of ASN behavior at the bureau of government and regional autonomy is pretty good Shown by the indicators of quality, quantity, cooperation, initiative and responsibility. Supporting factors are the motivation of each individual for career development and the existence of the BKD website, while the inhibiting factor is the new regulation or SOTK so that the disciplinary assessment is less effective. The advice given is to evaluate through counseling every month by the head of the sub-section and create a special attendance system for the Regional Government and Autonomy Bureau of East Java Province.